Implementation of group cognitive processing therapy in correction centers: Anticipated determinants from formative evaluation. Issue 1 (8th January 2023) - Zielinski, Melissa J.; Allison, M. Kathryn; Smith, Mollee K. Steely; Curran, Geoffrey; Kaysen, Debra; Kirchner, JoAnn E.
Abstract: Nearly all people in prison have experienced trauma, and many meet the criteria for posttraumatic stress disorder (PTSD). Untreated PTSD increases the risk of substance use problems after release, contributing to a well‐documented cycle of trauma, addiction, and incarceration. However, evidence‐based, trauma‐focused therapy for PTSD is rarely offered in prisons, and there is little research that can guide implementation efforts. In preparation for an effectiveness–implementation hybrid II pilot trial examining group‐delivered cognitive processing therapy (CPT) in prisons, we conducted a formative evaluation using interviews structured according to the consolidated framework for implementation research (i.e., CFIR). Participants were correction center leadership, treatment staff, health care staff, and security staff ( n = 22) and incarcerated persons ( n = 14; 57.1% female). We found that CPT was highly compatible with residents' needs and the centers' available resources, culture, existing programs, and current workflow. CPT was also acceptable to all stakeholders. Potential barriers were the lower relative priority for CPT compared with programs that are reinforced at the system level, limited staff time to deliver CPT, limited staff knowledge about PTSD, and center features that could distract from CPT groups and/or training or be countertherapeutic. Taken together, CPT is a promising trauma‐focused therapy for corrections, but these findings underscore the importance of identifying and matching potential barriers to effective implementation strategies a priori and work in the policy arena to promote sustainability.